Relationship Of Gardening Activities To Elderly Stress Level In Kuranji District Of Padang City - Afriyuni, Fera; Jumeno, Desto; Susanti, Lusi (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2022)
Aeing and physical decline in the elderly due to the degenerative process causes stress for the elderly. Humans evolved from helplessness to become a perfect man and independently, and eventually and do not know what to do facing advanced age. Almost all the events can be stressful. Gardening is one of the alternatives that can reduce the stress of the elderly. This research aims to find out the effect of gardening on elderly stress. This study’s design used purposive sampling techniques to disseminate questionnaires to as many as 237 seniors in Kuranji Sub-district of Padang City. The measuring instrument used to measure stress is PSS 10 and compares the frequency and duration of elderly gardening. The results were tested with the Wallis Kruskal statistical test with a value of p=0.034, with moderate stress levels and strength associated with the Spearman Rho test, with a correlation value of -0.236**. This study concludes that gardening effectively changes the stress levels of the elderly, so it is expected that the elderly do gardening as one of the non-pharmacology alternatives conducted independently without causing side effects.